Voluntary disclosure behaviour of annual report award winners. - Fua, Qiu Lin. (2008)
This research paper studies the voluntary disclosure behaviour of the Annual Report Award (ARA) competition winners for the period between 1996 and 2003. Specifically we study the extent of voluntary disclosure and the association between non-mandatory disclosures and the organizational characteristics of these companies.